2021
DOI: 10.4102/curationis.v44i1.2196
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the challenges in leadership roles experienced by nurse managers in a mining primary healthcare setting in South Africa

Abstract: Background: The challenges in leadership roles hinder the rendering of quality primary healthcare service in the mines. Mining, the heart of the South African economy, requires good health to its personnel to carry out operations. However, nurse managers, the leaders in a mining primary healthcare setting experience difficulties in their leadership roles.Objectives: The aim of this study was to explore and describe the challenges in leadership roles experienced by nurse managers in a mining primary healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Nurse managers often experience a number of challenges in leadership roles that affect the effectiveness of their leadership and the quality of primary PHC services rendered. 18 Similarly, the current study identified four challenges experienced by NMs with the use of KPIs in developing work plans. These included the knowledge of NMs regarding their expected role and function, training and support, resource allocation and exclusion of NMs from selected activities.…”
Section: Resultsmentioning
confidence: 71%
“…Nurse managers often experience a number of challenges in leadership roles that affect the effectiveness of their leadership and the quality of primary PHC services rendered. 18 Similarly, the current study identified four challenges experienced by NMs with the use of KPIs in developing work plans. These included the knowledge of NMs regarding their expected role and function, training and support, resource allocation and exclusion of NMs from selected activities.…”
Section: Resultsmentioning
confidence: 71%
“…Nurse managers who manifest emotional intelligence through democratic leadership styles are effective in implementing and maintaining organisational objectives and policies and findings associated well (40). A similar report from a study conducted by (41) indicated that nurse managers being part of most health management teams become conscious of the organisational system, hence their effectiveness in guiding subordinates and implementing organisational policies that help in achieving organisational goals and findings related well.…”
Section: Discussionmentioning
confidence: 86%
“…Lipsitch and Phil ( 2020 ) annotated that it was more difficult to triage patients in PHC during COVID-19, because a majority of them required a secondary healthcare intervention, and yet the hospitals were also full. Muller ( 2020 ) and Nene ( 2021 ) elicit that the COVID-19 trying times required strong leaders who are resilient, agile and supportive and who can be hands-on to ensure to improve service delivery.…”
Section: Resultsmentioning
confidence: 99%